Emergency Medicine CAQ review for physician assistants 2026-02-16T04:19:00+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Britnell, Jessica J.; Dodd, Hannah S. (Wolters Kluwer, 2016)

(untitled)
"The Emergency Medicine CAQ Review was written using the NACCPA emergency medicine content blueprint and it will include 250 multiple choice questions with rationales for correct and incorrect responses. The authors have secured the approval of the Society of Emergency Medicine Physician Assistants (SEMPA), which we can use in marketing materials and note on the cover. SEMPA has agreed to promote the book on their website and at their annual meeting"--Provided by publisher